REFORMING TAX POLICY FOR SUSTAINABLE ECONOMIC DEVELOPMENT IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2025)
Tax policy plays a vital role in shaping the economic development, fiscal stability, and investment climate of any nation. In the context of Uzbekistan, ongoing economic reforms have highlighted the need for a more efficient, equitable, and growth-oriented tax system. This article examines the current structure of Uzbekistan's tax policy, identifies its limitations, and explores potential strategies for reform in alignment with international best practices. Particular attention is given to the balance between direct and indirect taxation, the broadening of the tax base, the reduction of the informal economy, and the improvement of tax administration and compliance. Through comparative analysis and review of recent government initiatives, this study aims to offer practical recommendations for designing a tax system that supports macroeconomic stability, enhances public revenue mobilization, and promotes sustainable and inclusive growth in Uzbekistan.